Bidirectional Relationships between Peer Victimization, Loneliness and Solitude in Adolescence: A Systematic Review - González-Abaurrea, Eider; González-Cabrera, Joaquín; Ortega-Barón, Jessica; Escortell-Sánchez, Raquel; Machimbarrena, Juan Manuel (Adolescent Research Review, 2026)
Bullying victimization and cyberbullying victimization are pervasive phenomena with documented adverse psychological consequences. Although loneliness has been conceptualized as both an antecedent and outcome of victimization experiences, the nature of these relationships remains insufficiently understood. This systematic review synthesizes evidence on the relationships between bullying victimization, cyberbullying victimization, and loneliness, while examining conceptualizations and assessment of loneliness. Following PRISMA guidelines, 7253 articles were evaluated, including 100 studies meeting inclusion criteria. Selected studies included samples from a variety of countries, balanced in terms of gender and with ages ranging from childhood to adulthood. Most studies emphasized loneliness as distress arising from perceived deficiencies in social relationships, with measurement approaches varying considerably. The findings reveal complex, bidirectional relationships between victimization and loneliness, with stronger associations in adolescent samples compared to younger children or adults. While traditional bullying consistently demonstrated significant associations with loneliness, the cyberbullyingloneliness relationship showed greater variability. Some factors such as bystander behaviour or school connectedness moderated this relationship, being this protective effect stronger for girls. This review identifies critical gaps in understanding how different forms of loneliness interact with victimization across developmental stages and cultural contexts, providing a foundation for designing targeted interventions that address loneliness in victimized youth, particularly during adolescence.
Keywords: bullying; cyberbullying; peer-victimization; loneliness; solitude; adolescence; systematic review